Two opilionid species new to Finland: Opilio dinaricus and Mitostoma chrysomelas (Arachnida, Opiliones) - Annika Uddström; Veikko Rinne (Societas pro fauna et flora Fennica, 2025)
Two more opilionid species have been discovered since the latest checklist of Finnish Opiliones was published (Uddström et al. 2013). Specimens of Opilio dinaricus and Mitostoma chrysomelas were collected in 2014 and 2016 respectively. Both species were found in the same location in south-east Finland, on the island of Halla off the coast of Kotka. Neither one of these species were known from Finland before, the number of opilionid species recorded in Finland now being 17. Two specimens of M. chrysomelas were found under pieces of wood on a gravelly field. Several specimens of O. dinaricus were collected from a little grove. O. dinaricus was introduced to the Finnish readers already in the identification guide of Finnish Opiliones and Pseudoscorpiones (Uddström & Rinne 2016). On the island of Halla there are large fields used for storing raw timber shipped from Russia. Due to the nature of the site it is discussed if these species have established themselves in Finland.